Study of the soil atmosphere interaction and bearing capacity of a soil under desiccation (2017)
Dry environments produce layers of unsaturated soils that are frequently affected by cracks and shrinkage. These two phenomena can affect the stability of geotechnical works resting on the surface of the desiccated soil layers. Two points are relevant to the study of the effect of desiccation on soil layers and geotechnical structures: (i) the process of drying and its interaction with environmental variables, and (ii) the bearing capacity of soils affected by large cracks. Following this line of thinking, this thesis studies these two aspects. In the first part of this work the desiccation and cracking process of a thin layer of clay was studied experimentally using the climatic chamber at the Universidad de Los Andes. This chamber was improved to include a wind conduction system and a mechanism for heating and cooling the air in a close circuit. The evaporation tests were executed controlling air temperature, wind velocity, irradiance, and relative humidity. Tests were performed in the chamber at a field gravity of 1 g, imposing different environmental conditions and varying the thickness of the clayey soil. The second part of this thesis deals with the bearing capacity of soil affected by large cracks due to desiccation. A geotechnical centrifuge was used to model the influence of cracked soils and desiccation on the bearing capacity of shallow foundations. The reduced physical models fry to simulate the geometrical characteristics of the cracks in the Sabana de Bogotá in Colombia. A desiccated soil profile was simulated, approaching the field condition; soil models have an upper layer of over consolidated compacted soil resting on a normally consolidated layer. Models were tested at 50xg using the IFSTTAR robot which allows the use of different tools such as a cone penetrometer, a shallow foundation tool, and a spatula tool. Results show the effect of the cracks on the bearing capacity and the effect of desiccation along cracks. An analytical model is proposed to explain the experimental results. Also, the effect on the bearing capacity of the position of the load with respect to the cracks was studied